PENERAPAN METODE RAD PADA PEARNCANGAN SISTEM PEMBAYARAN ADMINISTRASI PEMBAYARAN JASA LAYANAN INTERNET PADA PT JARINGAN SARANA NUSANTARA - Rendi Setiawan; Fitri Latifah (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
PT Jaringan Sarana Nusantara an internet service provider, still uses a manual process to manage it’s paymaent system leading to problen such as recording errors and difficulties in tracking paymen history and status. This study aims to design and devlop a hinh-ferforming, stucture and efficient on line payment management system. The deploment methode used in Rapid Application Development (RAD). The result ini this system is the aoutomatic recording and facilityss tracking of customer payment